Introducing a new method for assessing short railway bridge conditions using vehicle onboard systems - Anna M. Rakoczy; Wojciech Karwowski; Monika Płudowska-Zagrajek; Maciej Pałyga (Archives of Civil Engineering)
Railway bridges are critical in the transportation network and vital to the profitability of the industry. Maintaining the bridge condition to safety standards is a priority for all railroad owners. However, the accumulation of damage that is not visible during regular inspections may cause catastrophic failures. The recent railroad bridge collapse over the Yellowstone River caused a train carrying toxic materials to fall into the river. The question arises “Could we predict and prevent this bridge collapse?”. The railroad bridge’s dynamic response under the train traversed can enable the assessment of structural conditions and may reveal structural issues that are not visible during the visual inspection itself. The onboard vehicle-based system is a novel concept that allows an autonomous evaluation of the existing railway bridge structures and substructures. An onboard system provides observations for multiple bridges, as opposed to a structural health monitoring system that is capable of monitoring only a single bridge. In 2016 the potential use of existing onboard systems to detect weak bridge stringers and changes in pier elevations was proved by a set of tests performed in the Transportation Technology Center (TTC) in Colorado, USA under controlled conditions. Recently, the research expanded to evaluate bridges in service. Several short, open-deck, railway bridges on the Polish Railway were examined using track geometry cars. The data were analyzed to compare and observe the changes in bridge response. This paper provides a summary of the findings of the analyzed data and future steps for research implementation.